Payment schemes and treatment responses after a demand shock in mental health care - Douven, Rudy; Remmerswaal, Minke; Vervliet, Tobias (Health economics, 2021)
We study whether two groups of mental health care providers—each paid according to a different payment scheme—adjusted the duration of their patients' treatments after they faced an exogenous 20% drop in the number of patients. For the first group of providers, self‐employed providers, we find that they did not increase treatment duration to recoup their income loss. Treatment duration thresholds in the stepwise fee‐for‐service payment function seem to have prevented these providers to treat patients longer. For the second group of providers, large mental health care institutions who were subject to a budget constraint, we find an average increase in treatment duration of 8%. Prior rationing combined with professional uncertainty can explain this increase. We find suggestive evidence for overtreatment of patients as the longer treatments did not result in better patient outcomes, i.e. better General Assessment of Functioning scores.